Early Marriage in the Perspective of Islamic Law: A Case Study in Indonesia - Kamal, Ahmad (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Early marriage is a persistent and complicated social issue, with a major contributing factor being out-of-wedlock pregnancies. This qualitative research, utilizing a case study approach, was conducted to meticulously examine the phenomenon of early marriage through the lens of Islamic law, based on concrete societal cases in Indonesia. The study sites were specifically chosen in the Yogyakarta and Kotabaru regions due to their high rates of early marriage. Data were gathered from 16 diverse informants, including early marriage practitioners, their parents, religious and community leaders, and officials from the Religious Affairs Office (KUA), using structured, in-depth interviews. Data analysis followed procedures of reduction, presentation, and interpretation. The research concluded with two significant findings: the dominant factors causing early marriage, where pregnancy outside of marriage is the most substantial cause; and the view of Islamic law in addressing this problem. The resolution often involves marrying the couple with considerations of public benefit (maslahah), adhering to the principles outlined in the Compilation of Islamic Law (KHI). While initial Islamic perspectives prohibit marriage after an act of adultery (zina), the use of marriage dispensation by religious courts allows for resolution, preventing issues related to lineage and further adultery. The research is highly beneficial for society as it clarifies the factors triggering early marriage, thereby facilitating the development of targeted, effective solutions and necessary legal reform.